STUDI FARMAKOFOR DAN DOCKING MOLEKUL RESEPTOR σ2 SEBAGAI TARGET PENGOBATAN KANKER PAYUDARA - Nursalam Hamzah; Haeria Haeria; Kamsia Dg Paewa (Universitas Islam Negeri Alauddin Makassar, 2015)
The σ2 receptor is an important target for the development of molecules in oncology because of its density (density) is ten-fold in proliferating tumor cells compared with tumor cells silence/benign (quiescent tumor cells) and also because of the observation that the σ2 receptor agonists are able to kill tumor cells through the mechanism of apoptosis and non-apoptotic. The purpose of this study is the Find features farmakofor compounds responsible for the activity and selectivity of σ2 receptor agonist. The procedure begins with the determination of farmakofor using MOE, 2009 to obtain the interaction between ligand and amino acids. Then performed molecular docking. Molecular docking also use MOE 2009 using thousands of compounds in a database downloaded from zinc. Results indicate amino acids that are important in the interaction with the ligand in the protein code is Gln725 and Asn719 (polar amino acids), and Arg766 (basic amino acids). The query farmakofor that play a role in the interaction of ligand-receptor features a group of donor and proton acceptor (F1: Don & Acc), group proton acceptor (F2: Acc), group proton donor (F3: Don) and the aromatic group (F4: Aro). The compounds that have potential as σ2 agonist activity based on the results of the virtual screening contained 10 compounds with ΔG = -19.6319 kkal/mol, -20.9598 kkal/mol, -19.2058 kkal/mol, -17.4499 kkal/mol, -22.4364 kkal/mol, -18.0056 kkal/mol, -5.5653 kkal/mol, -9.5687kkal/mol, and -9.8045 kkal/mol.